Production Potential, Moisture Use and Economic Viability of Pearl Millet (Pennisetum glaucum) Intercropped with Moth Bean (Vigna aconitifolia) under Rainfed Situations - Tetarwal, J P; Rana, K S; Ram, Baldev (Annals of Arid Zone, 2016)
A field experiment was conducted at research farm, IARI, New Delhi, in two consecutive rainy (kharif) seasons (2003 and 2004), on sandy loam soil to evaluate the effect of cropping system, fertility levels and moisture conservation practices on the productivity, moisture use and economics of pearl millet (Pennisetum glaucum) under rainfed conditions. Paired row of pearl millet (30/70 cm) + moth bean (1 row) intercropping system gave higher pearl millet grain equivalent yield (2960 kg ha-1), net monetary return (Rs. 8375 ha-1), monetary return efficiency (Rs. 107.37 ha-1 day-1) as well as WUE (8.34 kg ha-1 mm-1) and total rain use efficiency (4.79 kg ha-1 mm-1) than sole pearl millet. Application of 80 kg N + 40 kg P2O5 ha-1 produced significantly higher grain (2881 kg ha-1), stover yield (8278 kg ha-1), pearl millet grain equivalent yield (3140 kg ha-1), net monetary return (Rs. 9126 ha-1), monetary return efficiency, WUE and RUE over no fertilization, but statistically at par with 40 kg N + 20 kg P2O5 ha-1. Adoption of moisture conservation practices of FYM @ 5 t ha-1 + dust mulch + straw mulch resulted in significantly higher pearl millet equivalent yield, net monetary return, monetary returns efficiency and maximum WUE over rest of the moisture conservation practices. Key words: Pearl millet, moth bean, intercropping, fertility levels, moisture conservation, production potential, moisture use pattern, economic viability.